A qualitative study on the effect of game board strategy on the student's motivation of learning statistics course / Nurul Aityqah Yaacob... [et al.] - Yaacob, Nurul Aityqah; Ali, Rosemawati; Foo, Kien Kheng; Mohamed, Nadiah; Ahmad, Mardiana; Ahmad, Siti Noor Dina; Jamil, Nur Izzah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
An interactive teaching tool that utilizes a game board strategy to facilitate the learning of statistics has been developed and employed. This study aims to determine the impact of the board game on the motivation of diploma students towards learning statistics. Data are collected from 7 respondents using a face-to-face interview. Responses are qualitatively analysed. Results show that respondents are generally positive about the effectiveness of the board game as a teaching tool to enhance learning and understanding. More importantly, respondents have shown a change in attitude towards statistics and are more motivated to learn statistics under this innovative learning environment. Some suggestions for future research are outlined.